Planejamento, síntese e avaliação da atividade anti-SARS-CoV-2 e antitubercular de 4-amino-N-(4-benziloxibenzil)quinolinas. - Grams, Estevão da Silveira (2022)
COVID-19 and tuberculosis are infectious diseases caused by SARS-CoV-2 and Mycobacterium tuberculosis respectively. In the year 2020, these respiratory diseases were the biggest cause of deaths by a single etiological agent in the world. The emergence of more transmissive mutant strains of the virus and the lack of a treatment with recommended drugs highlight the urgent need for new therapeutic alternatives for these diseases. Due to the emergence of resistance of the tuberculosis strains, the development of antitubercular compounds is necessary. In this work, the novel series of 27 4-amino-N-(4-benzyloxybenzyl)-quinolines was synthesized with 26-48%yields. () For SARS-CoV-2, no inhibitory activity was observed against the virus, however, for TB, compounds with minimum inhibitory concentration (MIC) values in the range of 26.8-2.7 μM were obtained. The MIC results showed that the molecular volume of the halogenated group at the 6-position of the quinoline ring and the halogen attached at benzyloxybenzyl moiety represent two pharmacophoric groups. The lead compounds, 9n and 9o, MIC = 2.7 and 2.8 μM respectively, against M. tuberculosis H37Rv were selected for viability studies in Vero and HepG2 cells and showed selectivity to the bacillus. Thus, the results indicate that this class of compounds may present candidates for development of new alternative for the tuberculosis treatment.